PENGARUH KUALITAS PELAYANAN TERHADAP KEPATUHAN PEMBAYARAN PAJAK RESTORAN DI KOTA GORONTALO - Sri Susanda Amalia Putri; Andi Yusuf Katili; Ahmad Akmal Hi Syarta; Sofyaningsi J. Hasan; Agus Pariono (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
The purpose of this study is to provide an overview of restaurant tax payment compliance in Gorontalo City. The research method used is descriptive with a quantitative approach. A purposive sampling strategy was used to select 92 respondents as a sample for this study. The type of data used is primary data, which is the result of sending questionnaires to Gorontalo City restaurant tax payers. In this study, linear regression analysis was used with a partial test (t-test) to analyze the data. These findings indicate that compliance with restaurant tax payments is positively and significantly influenced by the level of service. The coefficient of determination of the study is 24.2%, which means that the service quality variable can take into account the restaurant tax payment compliance variable.